Current State of Knowledge on Invasive and Alien Fauna of Nepal - Budha, Prem Bahadur (Journal of Institute of Science and Technology, 2015)
This study produced a comprehensive list of introduced fauna of Nepal. Of the sixty four species of alien fauna reported, there were seven species of mammals with forty improved breeds of cow, buffalo, goat, sheep and pig, six species of birds with eight breeds of chicken and duck, nineteen species of fish, twenty two species of arthropods including one species of freshwater prawn and twenty one species of insects, nine species of molluscs and one species of platyhelminths. Among reported alien species Achatina fulica, Capra hircus, Clarius batrachus, Cyprinus carpio, Gambusia affinis, Oncorynchus mykiss, Oreochromis mossambicus, Oryctolagus cuniculus, Platydemus manokwari, and Sus scrofa are considered the worst species of the world and listed in ‘100 of the World’s Worst Invasive Alien Species’. The impacts of all these serious animals in Nepal are still to be studied but some problematic species of agricultural pests, freshwater habitat as well as livestock breeds are discussed in this paper. Journal of Institute of Science and Technology, 2015, 20(1): 68-81